Synthesis of Poly(butylene succinate) phosphorus-containing ionomers for versatile crystallization and improved thermal conductivity. (10th October 2018) - Xu, Yue; Zhang, Shuidong; Wang, Peng; Wang, Junsheng
Abstract: To explore the relationship between crystallization and properties of biodegradable ionomers for improving comprehensive performances, poly(butylene succinate) phosphorus-containing ionomers (PBSIs-K) with different ionic group content were synthesized by condensation polymerization of succinic acid, 1, 4-butanediol and phosphorous ion monomers (DHPPO-K). The chemical structures, experimental phosphorus content and intrinsic viscosities of PBSIs-K were determined by 1 H and 31 P NMR spectroscopy, inductively coupled plasma optical emission spectrometry and Ubbelohde viscometer, respectively. The effects of phosphorus-containing ionic group (PCIG) content on the thermal behavior, crystallization, rheological behavior of PBSIs-K were investigated by differential scanning calorimeter, polarizing optical microscopy, X-ray diffraction, rotational rheometer and dynamic mechanical analysis, respectively. They revealed that the crystallinity, grain diameter and spherulitic diameter of PBSIs-K initially increased and then reduced with the increase of PCIG content. The shear viscosity and Tg of PBSI7.5-K (7.5%PCIG content) increased due to physical crosslinking by ionic aggregates. Then the thermal conductivity, mechanical properties, hydrolytic degradation and gas barrier property of PBSIs-K were evaluated. The thermal conductivity of PBSI1-K (1%PCIG content) was strikingly promoted from 110 to 320 mW/m⋅k as the spherulitic diameter increased from 181 to 353 μm. Noteworthy, the elongation at breakage of PBSI7.5-K increased from 37% to 529% and the brittle-ductile transition was assigned to significant variations for PBSI7.5-K crystallization. Furthermore, hydrolytic degradation rate of PBSIs-K was dominated by PCIG content and was drastically accelerated when PCIG content ranged from 3% to 5%. The study revealed that the properties of PBSIs-K were dependent on PCIG content and provided a promising approach for biodegradable PBSI fabrication with versatile properties. Graphical abstract: Highlights: Poly(butylene succinate) phosphorus-containing ionomers (PBSIs-K) are synthesized by condensation polymerization. A small amount of PCI groups for PBSIs-K can facilitate the crystallization. The thermal conductivity and spherulitic diameter of PBSI1-K are promoted from 110 to 320 mW/m.k and 181 to 353 μm. A brittle-ductile transition for PBSIs-K can be observed when the PCIG content increases from 2.6% to 5.2%.